Plasmonic properties of two-dimensional metallic nanoholes fabricated by focused ion beam lithography - Zhu, Shaoli (2013)
Plasmonic metallic nanoholes are widely used to focus or image in the nanoscale field. In this article, we present the results of the design, fabrication, and plasmonic properties of a two-dimensional metallic pentagram nanohole array. The nanoholes can excite the extraordinary transmission phenomenon. We used the finite-difference time-domain method to design the transmission and the localized surface plasmon resonance electric field distribution in the near field. The focused ion beam method was used to fabricate the nanoholes. The transmittance in the far field was measured by a scanning spectrophotometer. The difference between the design and the experimental results may be caused by the conversion between the near field and the far field. The near field electric field distribution on the surface plasmonic nanoholes was measured by a near-field scanning optical microscope. From our results, we found that the maximum transmission of the nanoholes is 2.4. Therefore, our plasmonic nanohole can significantly enhance the transmission by exciting the plasmonic phenomenon on the surface of the nanostructures.